Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3844/ajbbsp.2020.15.24
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Relationship between ATP6 Gene and Sperm Motility in a Saudi Population

Abstract: Approximately 600 bp of ATP synthase subunit 6 mitochondrial gene (ATP6) were amplified and sequenced for 110 semen samples collected from infertile and normal Saudi men inhabiting Riyadh province. These data were analyzed in order to identify the Single Nucleotide Polymorphisms (SNPs) associated with male infertility. Six silent substitutions G8697A, G8856A, T8889C, T8952C, C9075T and C9060A were recorded with one novel site (G8856A) in the infertile men. Seven non-synonymous substitutions were also obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Associating the present results with the earlier studies, one can find worthy evidence for applying the ATPase 6 gene in differentiating between fertile and infertile men [65]. The sequence of MT-ATPase 6 gene revealed a high frequency of nucleotide changes in asthenozoospermic men.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Associating the present results with the earlier studies, one can find worthy evidence for applying the ATPase 6 gene in differentiating between fertile and infertile men [65]. The sequence of MT-ATPase 6 gene revealed a high frequency of nucleotide changes in asthenozoospermic men.…”
Section: Discussionsupporting
confidence: 85%
“…Bimah et al [ 64 ] confirmed that the frequencies of occurrence of the mutations at nts 8860 and 8701 were a hundred percent (100%) in both the normozoospermic and abnormospermic subjects. Elsanousi et al [ 65 ] sequenced the ATPase subunit 6 mitochondrial genes (ATPase 6) for infertile and normal Saudi men to identify the SNPs associated with male infertility. Seven non-synonymous substitutions were obtained with 4 novel sites (C8684T, G8860A, C8876T, and G9055A) in asthenozoospermic men.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the percentage of sperm motility showed a significant correlation to the frequency of that 7599 bp deletion [56]. There was a correlation between the Single-Nucleotide Polymorphisms (SNPs) and male infertility in a Saudi population [57].…”
Section: The Correlation Coefficient Of Amino Acid Mutation and Post-...mentioning
confidence: 97%